2005
DOI: 10.2223/jped.1375
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia and multiple osteolytic lesions in a child with disseminated paracoccidioidomycosis and pulmonary tuberculosis

Abstract: Objective: To describe the case of a child with paracoccidioidomycosis who presented hypercalcemia with multiple osteolytic lesions.Description: A 6-year-old boy was admitted with a one-month history of fever and hepatosplenomegaly. On admission, he looked sick, pale, and had disseminated lymphadenopathy and hepatosplenomegaly. The laboratory findings included anemia (hemoglobin = 6.8 g/dl), eosinophilia (1,222/mm 3 ), thrombocytopenia (102,000/mm 3 ), and hypoalbuminemia (serum albumin = 2.2 g/dl). Paracoccid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…The signs and symptoms presented by the majority of the patients from this cohort were related to the reticuloendothelial system, corresponding to the findings of other authors . Disseminated lethal cases affecting unusual organs and tissues with no clinical evidence were also observed in this study, confirming that the yeasts are capable to invade every tissue of the human body …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The signs and symptoms presented by the majority of the patients from this cohort were related to the reticuloendothelial system, corresponding to the findings of other authors . Disseminated lethal cases affecting unusual organs and tissues with no clinical evidence were also observed in this study, confirming that the yeasts are capable to invade every tissue of the human body …”
Section: Discussionsupporting
confidence: 90%
“…Patients with acute‐subacute PCM present disseminated fungal infection, frequently involving the phagocytic‐mononuclear system and leading to generalised lymphadenopathy and hepatosplenomegaly . The laboratorial typical findings are anaemia, eosinophilia, hypoalbuminemia and hypergammaglobulinemia, with high antibody titres in serologic tests …”
Section: Introductionmentioning
confidence: 99%
“…Hypercalcemia is well described in various granulomatous disorders; however, the association of P. brasiliensis and hypercalcemia is rare. To the best of the authors' knowledge, only two cases have been reported previously, neither of which offered a clear documentation of the etiology of the hypercalcemia [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few cases in the literature over the last 25 yrs which have reported children with hypercalcaemia associated with TB, often with severe disease (table 1) [4][5][6][7][8][9][10]. Our case describes a teenage female with extensive pulmonary TB associated with symptomatic hypercalcaemia that persisted despite cessation of vitamin D supplementation.…”
Section: Symptomatic Hypercalcaemia In Paediatric Tuberculosismentioning
confidence: 91%